Comparison in radiation tolerance between FLR planar junction termination and positive bevel edge termination for power diodes. (October 2022) - Liao, Xinfang; Liu, Yi; Xu, Changqing; Wang, Chen; Yang, Yintang
Abstract: In this paper, a coupled electro-thermal simulation model is established to investigate the single event burnout (SEB)-induced failure in power diode. The radiation tolerance of the two different termination structures, the field limiting ring (FLR) planar junction termination and the positive bevel edge termination, is revealed comparatively. Firstly, through the comparison in the SEB threshold voltage, our simulation results indicate that the positive bevel edge termination exhibits a stronger robustness to SEB. The difference in the anti-radiation performance can even reach 29.02% under the same ion incidence condition. Then, to fully understand why there is such a large difference in the radiation tolerance, we observed the entire failure process and obtained the SEB mechanism for the two termination structures. For the FLR planar junction termination, the edge of the main junction is the most sensitive region to SEB, since the high electric field here caused by the junction curvature effect can easily lead to the strong carrier multiplication and a large localized current density. By contrast, for the positive bevel edge termination, the electric field can be effectively reduced along the beveled surface, therefore, there is no electric field crowding at the edge of the pn junction. As a result, the positive bevel edge termination naturally exhibits a superior anti-radiation performance compared to the FLR planar junction termination structure. Highlights: The radiation tolerance of the termination structures for power diodes is researched comparatively for the first time. The positive bevel edge termination is more robust to SEB due to the improvement of the electric field at the chip edge. This article helps to get a better understanding of the SEB failure mechanism and the hardening design of power diodes.